To solve for r, we need to isolate r on one side of the equation. Let's simplify the equation step by step:
12 - 1/5r = 2r + 1
First, let's eliminate the fractions by multiplying every term in the equation by 5:
5(12) - 5(1/5r) = 5(2r) + 5(1)
This simplifies to:
60 - r = 10r + 5
Next, let's group all the terms with r on one side of the equation by adding r to both sides:
60 - r + r = 10r + r + 5
The -r and +r on the left side cancel out, and we have:
60 = 11r + 5
Now, let's subtract 5 from both sides to move the constant term to the other side:
60 - 5 = 11r + 5 - 5
This simplifies to:
55 = 11r
Finally, let's divide both sides by 11 to solve for r:
55/11 = (11r)/11
This simplifies to:
5 = r
Therefore, the solution is r = 5.
solve for r
12- 1/5r = 2r + 1
1 answer